Analisis Motivasi Belajar Matematika Secara Daring Pada Siswa Kelas XI SMA Negeri 1 Polokarto - Sri Mulyaningsih; Desi Arum Pramita; Suryo Krisworo; Afif Afghohani (Universitas Veteran Bangun Nusantara, 2021)
The objective of this study is to analyze the motivation to learn mathematics online on class XI SMA Negeri 1 Polokarto. The method is descriptive qualitative research. The subject is class XI SMA Negeri 1 Polokarto. The data collection technique is questionnaire about online mathematics learning motivation. The results of the analysis in this study indicate that students are mostly motivated by learning mathematics online. This can be seen from the objective indicator of intrinsic orientation which has a percentage of 90.93% and the goal of extrinsic orientation which has a percentage of 73.14%.